ADEQUACY OF COLLECTIONS IN MALAYSIAN AGRICULTURAL LIBRARIES - Majid, Shaheen; Ali Anwar, Mumtaz; S. Eisenschitz, Tamara (Malaysian Journal of Library and Information Science, 1998)
This study, using a questionnaire-based survey, explores the adequacy of library collections at five major agricultural research institutions in Malaysia. Data analysis revealed that their libraries are providing adequate information support to their scientists to sustain their research activities. However, a disparity was observed among these libraries for the adequacy of different types of materials. It was also found that involvement of library users in the selection of library materials is likely to improve their perceptions about library effectiveness in meeting their information needs. The study noted that purchasing power of Malaysian libraries has substantially decreased due to recent budget cuts and depreciated currency. The paper suggests various measures for improving library co-operation to effectively cope with the current economic slowdown.